PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS III SD GMIT AIRNONA 2 - Avy Bere; Jannes Bastian Selly; Kurniayu Triastuti R. A. Ratu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve student learning interest in IPAS learning through the application of the Problem-Based Learning (PBL) model assisted by Wordwall media. The background of this research is the low learning interest of students, as evidenced by their lack of participation, enthusiasm, and active involvement in the learning process. This research is a Classroom Action Research (CAR) conducted in two cycles with 24 students as research subjects. Data collection techniques included observations of teacher and student activities, as well as a student learning interest questionnaire. The results of the study indicate that the implementation of the Problem-Based Learning model assisted by Wordwall media was able to significantly increase students' learning interest, as evidenced by an increase in learning interest from 60.50% in Cycle I to 95.83% in Cycle II.From these results, it was concluded that the use of the Problem-Based Learning model assisted by Wordwall media was effective in increasing students' learning interest. This increase reflects that an interactive and contextual approach can stimulate curiosity and active participation of students in learning.